The Relationship Of Knowledge And Pregnant Women's Attitude About Pregnant Women Class At Sei Puskesmas Dadap Asahan District Year 2022 - Fithriani Fithriani (Jurnal EduHealth, 2023)
Pregnant women during pregnancy need knowledge about treatment, prevention, complications or complications during pregnancy and high-risk pregnancies through class activities for pregnant women. Constraints in the implementation of the class for pregnant women are the attitude of pregnant women and families who are classified as negative in attending classes for pregnant women. One of the negative attitudes of pregnant women is caused by a lack of knowledge. This study aims to determine the relationship between knowledge and attitudes of pregnant women about the class of pregnant women at the Sei Dadap Health Center, Asahan Regency in 2022. This research is a descriptive correlation research with cross sectional approach. This research was conducted from September 12, 2022 to September 24, 2022. The population was 118 people. Sampling using accidental sampling with a total sample of 320 people. The results of the study showed that the majority of pregnant women's knowledge about the class of pregnant women at the Sei Dadap Health Center, Asahan Regency in 2022, was mostly positive. Based on the results of the chi-square test, p value = 0.016 <0.05. The conclusion in this study is that there is a relationship between knowledge and attitudes of pregnant women about the class of pregnant women at the Sei Dadap Health Center, Asahan Regency in 2022. Suggestions in this study are the Sei Dadap Health Center of Asahan Regency continue to inform about the importance of class activities for pregnant women to avoid signs and dangers in pregnancy and the health of pregnant women is getting better.